Canopy evapotranspiration, leaf transpiration and water use efficiency of an Andean pasture in SE-Ecuador – a case study - Silva, Brenner; Strobl, Simone; Beck, Erwin; Bendix, Jörg (ERDKUNDE, 2016)
The relationship between canopy-level evapotranspiration (ETSci) and leaf-level transpiration (Tleaf) as well as photosynthesis (Pleaf) for a homogeneous tropical montane pasture was analyzed over five days using a combination of methods involving a laser scintillometer and a porometer. Weather conditions ranged from overcast to sunny during the period of study. The gas exchange of the leaves of the dominant pasture grass Setaria sphacelata (transpiration vs. photosynthetic CO2 net uptake ) was measured with a porometer and physiologically interpreted on the background of microclimate variables (photosynthetic active radiation (PAR) as proxy for total light intensity, temperature, water vapor deficit of the air) and soil moisture data. Water use efficiency (WUE, photosynthetic CO2 net uptake vs water loss by leaf transpiration) of the pasture was used to analyze the grass’ range of response to the environmental variables of the research area. PAR and water vapor deficit of the air (VPD) appeared to be the determinant factors for Tleaf and ETSci. WUE for the Setaria sphacelata pasture ranged from 1.9 to 5.8 µmol CO2 mmol-1 H20 day-1 and is particularly low during periods of high VPD combined with enhanced insolation during cloudless periods. ET measurements collected by the scintillometer demonstrated a strong correlation with water flux calculated using the Penman-Monteith approach (TPM) (r² = 0.95). Also, Tleaf measured with the porometer showed reasonable coincidence with the ET observations (r² = 0.78). Values of ETSci ranged from 2.26 to 4.96 mm day-1 and Tleaf ranged from 0.83 to 2.41 mm day-1, but only ETSci showed good correspondence with the available energy (net radiation). The lower correlation between Tleaf and canopy-level ETSci compared to that between ETSci and TPM was tested against contaminations from the adjacent fetch area of the scintillometer path, but no effects were found. Likewise, soil water limitations of Tleaf could be ruled out. Therefore, different correlations of ETSci and Tleaf with the incoming energy and VPD may be traced back to a direct effect of the VPD on ET in contrast to its indirect effect on Tleaf which is additionally regulated by physiological processes in the leaf stomata.